IS SEX WORTH DYING FOR? Sentimental-Homicidal-Suicidal Violence in Theological Discourse of Sexuality - Rees, Geoffrey (Journal of religious ethics, 2011)
In theological discourse of sexuality, queer theory has often been regarded as an extension of the project of gay and lesbian liberation, when it actually challenges an organizing value of the entire discourse, because it challenges any ascription of ultimate value to “sex,” an imaginative formation of power relations. Rather than appeal to God to authorize the privileged status of sex, queer commentary suggests that theological writers should refuse assertions of the absolute importance of any particular formation of human imagination as a basis of relation between self and God. The goal is to recognize the violence—symbolized and real—that enforces the worth of certain imaginations of intelligibly sexed personal identity and stunts the formation of alternative imaginations of intelligible personal identity. Critical account of this violence as sentimental-homicidal-suicidal opens space to confess a theological discourse of personal identities that is entirely beyond sex.